Industry influence and agency decision making: Evidence from USAID - Vincent H. Smith; Philip G. Hoxie (American Enterprise Institute (AEI), 2021)
This paper examines the avenues interest groups use to influence procurement decisions that are subject to legislative constraints that conflict with the provision of the government service or goods, such as "Buy American Laws." We first explore a theoretical model in which the government agency can value service of the interest group and fulfilment of its procurement. We then examine the implications of this theoretical model empirically using data on the US Agency for International Development's Title II Emergency Food Aid program for the shipment of packaged goods to low income countries facing humanitarian crises. We find that USAID, which is subject to a type of "Buy American Law" called cargo preference when allocating food aid, at times over-complies with the mandate. We then use an empirical approach to gain insights into how USAID makes allocation decisions in accordance with its compliance with the mandate throughout the fiscal year.
Keywords: A; 330; Rent-seeking; Bureaucracy; Procurement; Disaster Aid